The influence of creativity on competence marketing and it’s implications on capital investment collection - R Susanto Hendiarto; Ghesty Kania (Institute of Computer Science (IOCS), 2023)
The current problem is that the accumulation of capital investment in the West Java Kadin-assisted MSME community is still in a slump during the COVID-19 pandemic, this is suspected because MSMEs do not yet have marketing competence, especially in terms of digitization, even though in the conditions of the COVID-19 pandemic where interactions are completely limited, then digitalization competence for MSMEs is a necessity, having the ability and even competence in the field of marketing requires the creativity of MSMEs which are currently not evenly distributed and entrenched in the MSME environment. This study aims to determine the effect of creativity on marketing competence and its implications for raising capital investment, a case study on Kadin Jabar's business in Bandung. The research method applied was in the form of an analytical descriptive survey method, while the sample used was 42 respondents. The variables examined from each respondent are creativity, marketing competence, and capital investment accumulation. The type of data collected is primary data. The results of the study show that creativity has no effect but has a significant value on marketing competence. The object of this research is that the respondent sample used is still limited to the West Java Kadin assisted businesses in Bandung, therefore it is necessary to carry out further research based on a more varied sampling with a longer duration, so that results can be generalized.